Technology Readiness in English Language Teaching: Analyzing Gaps and Barriers - Kau, Magvirah El Walidayni (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2024)
The integration of technology in education, particularly in English Language Teaching (ELT), has become a crucial element of 21st-century pedagogy. However, significant gaps and barriers impede the effective adoption of technology by teachers. This study investigates the technology preparedness of English language teachers in Indonesia, focusing on the challenges they face in integrating technology into their teaching practices. Using a qualitative research design, data were collected through semi-structured interviews with English language teachers in a rural area. The findings reveal that while teachers perceive technology as an essential tool for enhancing instruction and exhibit confidence in its use, they encounter significant obstacles such as limited access to resources, inadequate infrastructure, and insufficient professional development. These barriers not only affect teaching efficacy but also hinder students' engagement and learning outcomes. The study underscores the necessity of addressing these challenges through targeted professional development and systemic support. By aligning the findings with frameworks such as the Technology Acceptance Model and Constructivist Learning Theory, this research highlights actionable strategies for policymakers and educational institutions to foster a more conducive environment for technology integration. The implications of this study extend to improving the quality of English language instruction and preparing students for the demands of a digitally-driven world.